Decreased Arterial Elasticity in Children With Nondialysis Chronic Kidney Disease Is Related to Blood Pressure and Not to Glomerular Filtration Rate. Issue 4 (October 2015) - Sinha, Manish D.; Keehn, Louise; Milne, Laura; Sofocleous, Paula; Chowienczyk, Phil J.
<x xml:space="preserve">Abstract</x> We compared large artery mechanical properties in children with nondialysis stages of chronic kidney disease with those in children with normal renal function, examining the potential effect of blood pressure (BP) components and level of renal dysfunction. Common carotid artery mechanical properties, carotid-femoral pulse wave velocity, and carotid and peripheral BP were measured in children (n=226) with nondialysis chronic kidney disease (n=188; 11.9±3.7 years; 26%, 25%, 30%, 16%, and 3% in stages 1, 2, 3, 4 and 5, respectively) and healthy controls (n=38; 11.5±3.3 years). In children with nondialysis chronic kidney disease when compared with healthy controls, at similar levels of peripheral and carotid BP, carotid artery diastolic diameter and wall thickness were similar. In those with suboptimal BP (≥75th percentile), indices of arterial elasticity indicated greater stiffness than in healthy normotensive controls (distensibility: 92±31 versus 114±33 kPa−1×10−3, P=0.03; compliance: 2.1±0.7 versus 2.6±0.7 m2 kPa−1×10−6, P=0.02; Young elastic modulus: 0.151±0.068 versus 0.109±0.049 kPa×103, P=0.02; and wall stress: 83.6±23.5 versus 68.7±14.9 kPa, P=0.02). In all children, mechanical properties were independently related to carotid and peripheral BP components but not to estimated glomerular filtration rate. In children with nondialysis chronic kidney disease, changes in elastic properties of the carotid artery are primarily related to BP and not to glomerular renal function.